Problem-based Learning: Improving Students’ Concept Mastery and Learning Activities - Susanti Bili; Suparmi Suparmi; Sarwanto Sarwanto (Journal of Educational Science and Technology (EST), 2022)
Concept mastery is the based ability of higher-order thinking skills in the era of society 5.0. Increased understanding of the concept is in line with the practice of dependent on active learning activities by students. The purpose of the study was to determine the effect of problem-based learning on the concept mastery and learning activities of students. The research method used is a quasi-experimental research design with a non-equivalent pretest-posttest control group. The sample had selected through purposive random sampling. The instrument used is a conceptual understanding test instrument with an indicator of adaptation knowledge dimensions from Bloom's taxonomy and a learning activity instrument of a questionnaire. In the results of this study, there are differences between the experimental class and the control class on understanding concepts and learning activities of students; the PBL model increase students' concept mastery